PH triggered in-situ ophthalmic gel containing nepafenac: formulation, characterization and in vitro drug release / Ikhwan Hadi Suhaime - Suhaime, Ikhwan Hadi (2015)
Amongst the different delivery methods to the eye, an in-situ forming hydrogel is considered as one of the most effective delivery methods. An in-situ forming hvdrogel is a formulation that can undergo gelation in response to the variations in its external environment. The pH triggered in-situ ophthalmic gel systems have been widely investigated in regard to their spontaneity of gelation, gel system characterization, invitro drug release and ophthalmic compatibility. However the involved energetics and thermodynamics related to the phenomenon of sol-gel transition have been investigated sporadically. Hence the present study aimed to examine and elucidate the involved energetics and thermodynamics during the sol-gel transitions of carbopol in the presence of viscosity-enhancing agents such as Hydroxypropyl Methylcellulose (HPMC) and surfactant such as Benzalkonium chloride (BKCL). Using viscometric and conductometric titration, various concentrations of carbopol and carbopol-based solution systems in the presence of HPMC and BKCL were analyzed to determine the thermophysical parameters such as molar conductivity (k), activation energy (E*), enthalpy (AH), entropy (AS), Gibb’s free energy (AH) and heat capacity (ACP) of the systems. These parameters were discussed in terms of the phenomena of sol-gel transitions, emphasizing the effect of polymer concentration and the presence of coexcipients such as HPMC and BKCL. Based on the thermophysical experimentations, the suitable concentrations of carbopol, HPMC and BKCL was selected for use in the optimized formulation. The optimized formulation was achieved by incorporating buffering agents such as citric acid and sodium dihidrogen phosphate, and various concentrations of chitosan for added anti-microbial and mucoadhesive activity. The formulation optimization was carried out on the basis of parameters such as viscosity, surface tension and spontaneity of gelation. The pH adjustment was done by varying the concentration of sodium hydroxide and accordingly the suitable formulations were selected. The drug nepafenac was investigated as a model drug .The optimized formulations were further characterized for the in-vitro drug release study. The data related to drug release studies were treated using the release kinetic models and the optimized in-situ gel resulted in a controlled release (with a release index of 0.538 for Fu) of the candidate drug nepafenac.